One woman's liberating : the life and career of Estefania Aldaba-Lim - Joaquin, Nick. (Pasig City : Anvil, 1996)
An eyrie with a balcony overlooking boulevard and bay; meriendas of hot crispy lumpia with tart cheese and cold beer; lazy conversations where gradually the reminiscences predominate and get set down -- such was the genesis of this book, of which the material (memories of various lives as a girl and dame, as daughter and mother, as learner and doer) unavoidably savors of pale pilsen, cheese on crackers, and crunchy lumpia, as well as of salty sun and zephyr on a balcony high, high up in space. A coffee-table book? Well, no. More like a merienda-table book: an eatable read
1. The reluctant cabineter -- 2. Childhood in Barrio santo Rosario -- 3. Reading and Riting and Rithmetic -- 4. Collegiate at PWU -- 5. The simultaneous -- 6. Outward Bound -- 7. This side of paradise -- 8. Racing with war -- 9. A community in exile -- 10. Romance in wartime -- 11. Bellona's Epithalamium -- 12. War and Peace -- 13. The IHR and How it grew -- 14. Return of the profesora -- 15. The post-bellum scene -- 16. With Mom and dad in San Lorenzo -- 17. The extra curricula -- 18. No More Key -- 19. Madame -- 20. DSW into DSSd -- 21. The hazards of government service -- 22. Six Years Plus Five -- 23. The Body of the UN -- 24. Touring the global Village -- 25. Cloud Nine.
Keywords: WOMEN PUBLIC OFFICERS -- PHILIPPINES -- BIOGRAPHY